Jenny Thompson's Arm Action at 70 m of Her 100 m Freestyle Gold Medal Race at the 1998 Perth World Championships - Rushall, B. S.
Video pictures (18 frames) and the appropriate technical/ biomechanical explanations for Jenny Thompson's Arm Action at 70 m of Her 100 m Freestyle Gold Medal Race at the 1998 Perth World Championships. Jenny Thompson's stroke is relatively simple. Her entries are well in front of the head and stretch forward and downward. She executes direct thrusts backward using the hand/forearm as propelling surfaces. Body movements occur to accommodate the restrictions of her anatomy for developing efficient direct propulsion. It appears that the breathing action does alter length forward and directness of pull in the left arm. By holding the head up to look forward the resulting neck flexion limits the extent of elevation of the left shoulder which in turn shortens forward length. A breathing action that only rotates laterally would be a possible improvement. Jenny Thompson still remains the fastest "clean" swimmer in history. She truly does "crawl" through the water.